The automatic implantable cardioverter/ defibrillator: transesophageal atrial pacing discloses the potential for erroneous discharges. - Critelli G; Monda V; Scherillo M; Coltorti F; Greco C; Reale A (Pacing & Clinical Electrophysiology, 1988)
We report the occurrence of erroneous discharge from an implanted automatic cardioverter/defibrillator during transesophageal atrial pacing. Transesophageal pacing was performed as part of a study protocol on the inducibility of ventricular tachycardia from the atrium in patients with ischemic heart disease. At on induced heart rate of 166 beats per minute (a value just above the cut-off rate of the device), the cardioverter/defibrillator was triggered. This observation suggests that transesophageal atrial pacing could be utilized to disclose the potential [or spurious discharges in the event of fast atrial rhythms in patients with the automatic implantable cardioverter/defibrillator.